The future of humanity : from global civilization to great civilization - Jin, Zhouying (ISSN., 2022)
Additional Prefaces from Theodore Jay Gordon, Hazel Henderson, Randeep Sudan, and new original material in each chapter. Considers impact of Covid-19 and influence beyond health and hygiene, impact on economic, social and geopolitical affairs, and the need to change established behaviour patterns including lifestyle, working practices and diet.